PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BIMA - IRA JULFIYATI; MUKHLIS (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Abstract. This study aims to determine the effect of communication and motivation on employee job satisfaction at the Office of Public Works and Spatial Planning, Bima Regency. The approach used in this research is using an associative approach. The sample in this study was 89 respondents. The data collection techniques used were observation, questionnaires, and literature study. Data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, t tests, and F tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. Partially, The results of the study show that communication has no significant effect on job satisfaction and motivation has a significant effect on employee satisfaction at the Public Works and Spatial Planning Office of Bima Regency. The results of the study show that communication and motivation simultaneously affect employee job satisfaction at the Office of Public Works and Spatial Planning in Bima Regency. by 64.2%.